Contemporary healthcare experience in Malaysian Hospitals - Hasliza Hassan, Hassan; Rahman, Muhammad Sabbir; Abu Bakar , Sade (North American Business Press, 2016)
The main dissatisfaction of patients in hospital is the long waiting time, which could lead to stress. This research makes suggestions concerning how to reduce the impact of the negative perception about the lengthy waiting time by having a contemporary healthcare experience through sub-retailers and nursery services within the hospital. It is highly expected that the enhancement of the basic healthcare concept through sub-retailers within the hospital will create a more relaxed feeling while waiting for medical treatment. In addition, it is suggested that nursery services would also provide more convenience for the patients.